(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper presents the problem of different forms of nomadism of Milena Pavlović Barilli (1909-1945), the painter and poet who created in the interwar period. She circulated between Serbian and Italian, German and French, Spanish and American languages and cultures, enriching her artistic work by the elements of all of them. The first part of the article recalls definitions of nomadism as an intellectual and artistic way of thinking and creating given by Zygmunt Bauman, Gilles Deleuze and Félix Guattari and Rosi Braidotti, the author of the fundamental book Nomadic Subjects. The following parts of the paper introduce the typology of different forms of Pavlović Barilli’s nomadism. Six main nomadic forms are suggested and analyzed: her national/ethnic nomadism, her language nomadism, the artistic/esthetic nomadism, the gender nomadism and the cultural one.